Campaña social como aporte a la concientización del acoso escolar en la Unidad Educativa Baños - López Ramos, Bryan Saúl (2023)
Bullying is a social problem that has affected children and adolescents in different educational establishments in the region, for this reason this project covers this problem from the social area, seeking to identify the factors that most prevalently affect the students of the Baños Educational Unit in the province of Tungurahua, to better understand the problem that is experienced in the institution, a mixed approach was carried out, using instruments such as the interview and the survey of experts on the subject such as the psychological department of the institution and the teachers in charge of the students with the purpose of raising awareness. Raise students by fostering empathy and obtain more information about the cases that exist in the institution to develop strategies that support the campaign and help to face the problems that the institution experiences due to school bullying.